2021
DOI: 10.3390/su13116497
|View full text |Cite
|
Sign up to set email alerts
|

Interval Type-2 Fuzzy Super SBM Network DEA for Assessing Sustainability Performance of Third-Party Logistics Service Providers Considering Circular Economy Strategies in the Era of Industry 4.0

Abstract: Stakeholders are increasingly aware of the aspect of sustainability, and the fact that the circular economy facilitates the achievement of sustainable development goals. They place pressure on supply chains to become sustainable, and for this reason, third-party logistics (3PL) service providers, as specialized professionals, play a vital role in sustainable supply chain management. Although developments in technology in the era of Industry 4.0 have been effective at directing 3PLs along the path towards susta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 76 publications
(123 reference statements)
0
7
0
1
Order By: Relevance
“…In this context, it is important to predict customers' expectations and the environmental impacts resulting from these expectations [3,10]. This process seems to be indispensable for reducing unfavorable climate changes, which have increased with the development of production (Industry 4.0) [12,13]. Hence, it is necessary to propose a model for the prediction of pro-quality decisions while considering sustainable development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it is important to predict customers' expectations and the environmental impacts resulting from these expectations [3,10]. This process seems to be indispensable for reducing unfavorable climate changes, which have increased with the development of production (Industry 4.0) [12,13]. Hence, it is necessary to propose a model for the prediction of pro-quality decisions while considering sustainable development.…”
Section: Discussionmentioning
confidence: 99%
“…From a pro-environment standpoint, the quality level should include environmental aspects, i.e., the consideration of all organization activities and products that can impact the environment [11]. However, the dynamics of the market, including the industrialization of enterprises (Industry 4.0) [12,13], have generated the need for the sustainable development of products ahead of the competition [1]. This requires the prediction of product quality level and its possible impact on the natural environment.…”
Section: Introductionmentioning
confidence: 99%
“…(2021), and Pishdar et al. (2021), proposed the inclusion of intermediate variables in the objective function. It was observed that in the last six years, there were publications that considered this point, with the increasing presence of models with intermediate variables in the efficiency measure, which may indicate a line for refinement in future research.…”
Section: Further Research Directionmentioning
confidence: 99%
“…The "systemic vision" axis enables the identification and holistic analysis of the company's strengths and eventual economic, social, and environmental vulnerabilities (Verhulst and Brenden, 2021), while the "stakeholders" axis brings elements that strengthen the company's relationships with members of the value chain, with shareholders, with the internal public, and with society in general, by providing transparency regarding sustainable corporate initiatives (Satyro et al, 2021). In turn, the "governance" axis brings elements that help both in decision making in a reliable way and in monitoring the use of resources and carrying out activities focused on sustainability issues, contributing to the fulfillment of the company's goals (Pishdar et al, 2021). Although these elements are important in the company's transition to CS, the "governance" axis showed an imbalance among the TBL dimensions, with fewer elements addressing the social aspect.…”
Section: Imbalance Of Social Elementsmentioning
confidence: 99%